Analysis of Computer based Management Information Systems in the Decision Making Process - Utami, Batina Yulia; Sabandi, Ahmad; Irsyad, Irsyad (Postgraduate School, Universitas Negeri Padang, 2024)
Computer-based management information systems mean that computers play an important role. An organization's technical capabilities, or an organization's ability to adapt to internal and external conditions, are critical to organizational success.In the midst of rapid technological advances, using Management Information Systems is the best way to manage high-quality information resources. The management role requires the effective deployment and use of resources to achieve specific goals. As a result, this task will help management by providing information quickly and precisely. To support company goals, an effective management information system is needed. In reality, the term